Defect engineering oxygen vacancies via synergistic tungsten substitution and water quenching in V2O5 cathodes for high-performance zinc-ion batteries - Jianwei Wang; Lin Xu; Yating Yu; Jianzhao Liu; Qianhui Zhang; Wenlin Zhang; Xinyue Wang; Jihong Bian; Yanzhong Zhen; Daniel Q. Tan (Chemical Engineering Journal, 2026)

Semiconducting polymer-based ratiometric fluorescent nanoprobe for highly accurate imaging of H2S in inflammatory and tumor cells - Chen Han; Xing Wang; Yating He; Rong Wang; Hong-Min Meng; Lin Zhang; Zhaohui Li (Analytica Chimica Acta, 2026)

Spatiotemporal photothermal heating and dynamic alkaline buffering work together to achieve programmable degradation of PLLA bone scaffolds - Wei Wen; Jinyan Liu; Yating Lin; Yuchen Hou; Shan Ding; Cairong Li; Yuxiao Lai; Binghong Luo (Chemical Engineering Journal, 2026)

Interaction dynamics in a network of winter climate drivers in Northeast Asia - Lvyi Zhang; Yating Lin; Geli Wang; Anastasios A. Tsonis; George Sugihara (Stochastic Environmental Research and Risk Assessment, 2026)

Social context modulates the behavioural effects of physical enrichment in yellowfin seabream Acanthopagrus latus - Yijie He; Zonghang Zhang; Yating Zheng; Wuhan Lin; Wentao Lu; Qiaoling Fu; Wenhua Liu (Applied Animal Behaviour Science, 2026)

Enhancing the postharvest resistance to Monilinia fructicola of flat peach by plasma-processed air induction: Based on activating antioxidant metabolism and accumulating disease-resistant metabolites - Baoxiang Li; Xiaomin Yang; Ziya Lin; Yatao Yin; Yating Zhao; Xianghong Meng (Postharvest Biology and Technology, 2026)

The aging eye: navigating molecular mechanisms and innovative interventions - Yumeng Lin; Zhongyu Han; Yunfeng Zhang; Ruimin Yuan; Mingyu Huang; Yating Liu; Jun Wang; Chen Xu; Luze Liu; Ping Yu; Qingsong Yang; Liuzhi Zeng; et al. (Biogerontology, 2026)

The dominant role of amylose content in regulating the multiscale structure of hydroxypropyl distarch phosphate for 3D printing ice cream - Minghao Xu; Yating Xu; Shengyang Ji; Yonghao Liu; Diyi Zhang; Lin Feng; Yinliang Wu; Peng Zhang; Jianfu Shen; Baiyi Lu (Food Hydrocolloids, 2026)

Building 3D conductive networks within sponge-like porous carbon nanofibers: A CNT-based cathode strategy for superior microbial fuel cells - Wei Huang; Yating He; Wenyi Yan; Longfei Qiao; Yu Tao; Xiangyu Wei; Xiumei Song; Lin Yang; Lichao Tan; Xin Wang; Zhongwei Chen (Chemical Engineering Journal, 2026)

High-efficiency enzymatic conversion of cellulose to starch by strengthening glucose-utilization bypass - Yuanyuan Zhang; Menglong Chen; Yating Wang; Zhenwei Xiong; Keqiang Xu; Xinyu Liu; Hui Lin; Quanjun Liu; Hongge Chen (Bioresource Technology, 2026)

Magnesium Ions Promote the Apoptosis of Cervical Cancer Cells through the PI3K/AKT/FoxO1 Pathway - Qian Zhao; Wang Yang; Lingling Cao; Yating Chen; Wumuti Baheti; Chen Lin (Biological Trace Element Research, 2026)

Co(salen)-based hyper-crosslinked porous ionic polymer as heterogeneous synergistic catalyst for the cycloaddition of CO2 with epoxides - Yaju Chen; Yongjian Qiu; Zhitong Wang; Xiaoxue Zhou; Haowen Chen; Lin Lei; Yating Wang; Hongbing Ji (Fuel, 2026)

Alloy-sulfide co-engineered thin Li anodes suppress dead-Li for practical high-energy-density lithium metal batteries - Qiyang Chen; Jing Zhu; Yuanfan Zhao; Wenrui Zheng; Hanqing Pan; Yinlong Lin; Yating Ke; Xinghui Wang (Chemical Engineering Journal, 2026)

PQS signaling and temperature variation modulate phage infection in Pseudomonas aeruginosa: Implications for foodborne pathogen control - Yinfeng Wang; Jiuna Kong; Yating Chen; Hong Lin; Xiuping Jiang; Guanhua Xuan; Jingxue Wang (International Journal of Food Microbiology, 2025)

Impact of Autumn Arctic Sea Ice concentration on Siberian High: Insights from causal relationship - Yating Lin; Geli Wang (Atmospheric Research, 2025)

Association of air pollution exposure and habitual physical activity with risk of overall and cause-specific hospital-treated infections: a UK Biobank cohort study - Zixuan Jiang; Yahang Liu; Yifang Huang; Chen Huang; Yating Yang; Ruilang Lin; Jing Wang; Runzhi Bai; Xueying Zheng; Yongfu Yu; Guoyou Qin (Environmental Research, 2025)

Northern annular mode and Northeast Asian temperature anomalies: exploring causality and the causes of its non-stationarity - Yating Lin; Geli Wang; Anastasios A. Tsonis (Climate Dynamics, 2025)

One-pot synthesis of highly stable CsPbBr₃@C6H7NO3S composite and its application in nitrite fluorescent sensing - Yongzhen Qiu; Yexin Zu; Yating Zhang; Yue Lin; Fang Luo; Zuquan Weng; Cuiying Lin; Jian Wang; Bin Qiu; Zhenyu Lin (Food Chemistry, 2025)

On-site tracking of trace Aflatoxin B1 in food waste composting via a portable colorimetric sensing platform with nanozymes - Yating Lu; Fuqing He; Xu Zhu; Jing Tang; Yue Lu; Jiajia Wang; Jiangfang Yu; Li Chen; Xingyang Cheng; Tianhao Liu; Lin Tang (Journal of Hazardous Materials, 2025)

Ratiometric fluorescence analysis of tetracycline by dual-ligand europium-based metal-organic framework - Yating Zhong; Keying Zhang; Xinru Wang; Haibo Liang; Ying Yu; Manli Guo; Yujuan Cao; Bixia Lin (Food Chemistry, 2025)

Mechanism of Epigallocatechin-3-gallate in the prevention and treatment of irritable bowel syndrome: A network pharmacology and gene expression omnibus chip data-based study - Fangchen Ye; Laifu Li; Lianli Wang; Yan Ran; Lin Mei; Yating Sun; Xinping Zhang; Fei Dai (PharmaNutrition, 2025)

A rapid and sensitive paper-based sensor for sulfide ion detection in Chinese liquors - Lichao Lin; Lusha Wu; Yating Wang; Zhou Jiang; Jian Wang (Food Chemistry, 2025)

Unraveling the complexities of ozone and PM2.5 pollution in the Pearl River Delta region: Impacts of precursors emissions and meteorological factors, and effective mitigation strategies - Yating Chen; Liye Zhu; Sihui Wang; Daven K. Henze; Tzung-May Fu; Lin Zhang; Xiaoling Wang (Atmospheric Pollution Research, 2025)

Transparent mechanism of salted egg (white) hierarchically and synergistically driven by NaCl, NaOH and thermal treatment: Based on empirical data and molecular simulation - Le Chen; Shiqin Dong; Peng Xu; Zhuosi Yu; Yating He; Yongle Liu; Xiaole Xiang; Qun Huang; Shugang Li; Lin Ye (Food Chemistry, 2025)

Development and antimicrobial activity of composite edible films of chitosan and nisin incorporated with perilla essential oil-glycerol monolaurate emulsions - Zhantong Fang; Yating Yang; Shuimu Lin; Lirong Xu; Shuyi Chen; Wanxia Lv; Nannan Wang; Shiyi Dong; Chunhong Lin; Yutao Xie; Jingru Liu; Meihan Meng; et al. (Food Chemistry, 2025)

Construction of Zinc-based metal-organic frameworks for visual ratiometric fluorescence detection of tetracycline - Yating Zhong; Haocheng Gao; Jingqi Yang; Xinru Wang; Ying Yu; Yujuan Cao; Manli Guo; Bixia Lin (Analytica Chimica Acta, 2025)

Probing fragile topology with dislocations - Ying Wu; Zhi-Kang Lin; Yating Yang; Zhida Song; Feng Li; Jian-Hua Jiang (Science Bulletin, 2024)

Effects of pre-chlorination on ultrafiltration process in directly treating seasonal high-turbidity surface water: Membrane fouling control and shock load resisting - Haochun Wang; Yaru Zhang; Chenghai Lin; Ao Wang; Yanrui Wang; Yating Hu; Shu Jiang; Jinlong Wang; Heng Liang; Xiaobin Tang (Journal of Water Process Engineering, 2024)

Contrasting orbital rhythms preserved in loess grain-size records across the Chinese Loess Plateau - Deai Zhao; Guoqiao Xiao; Chunju Huang; Haibin Wu; Qingzhen Hao; David B. Kemp; Shaohua Tian; Zhipeng Wu; Hao Lu; Gaowen Dai; Shuzhen Peng; Changyan Tang; et al. (Global and Planetary Change, 2024)

Optimization study on circadian tunability and Rec. 2020 of RGB-LED-based displays considering the users with different ages - Qinzhen Lin; Ruoping Lian; Haoyang Liu; Wenhui Li; Junying Li; Yating Feng; Yi Lin; Suyao Liu; Weijie Liu; Kaiyu Yang; Yinxiao Yang; Yaling Chai; et al. (Energy and Buildings, 2024)

Sensitive and quick electrochemiluminescence biosensor for the detection of reactive oxygen species in seminal plasma based on the valence regulation of gold nanoclusters - Lingjun Cheng; Yuanyuan Yang; Shaobin Lin; Canping Su; Mingming You; Yating Liu; Qingfei He; Jiaming Chen; Zhenyu Lin; Guolin Hong (Analytica Chimica Acta, 2024)

Inclusion of Lonicerae flos improved anaerobic fermentation and antioxidant activity of mixed silage (agro-residue and alfalfa) - Lin Mu; Xin Cao; Yating Wang; Qinglan Wang; Zhifei Zhang (Animal Feed Science and Technology, 2024)

Exploring a specialized programmed-cell death patterns to predict the prognosis and sensitivity of immunotherapy in cutaneous melanoma via machine learning - Leyang Xiao; Ruifeng He; Kaibo Hu; Gelin Song; Shengye Han; Jitao Lin; Yixuan Chen; Deju Zhang; Wuming Wang; Yating Peng; Jing Zhang; Peng Yu (Apoptosis, 2024)

Risk analysis of air pollutants and types of anemia: a UK Biobank prospective cohort study - Laifu Li; Yan Ran; Yan Zhuang; Lianli Wang; Jiamiao Chen; Yating Sun; Shiwei Lu; Fangchen Ye; Lin Mei; Yu Ning; Fei Dai (International Journal of Biometeorology, 2024)

Enhancing antitumor efficacy of NIR-I region zinc phthalocyanine@upconversion nanoparticle through lysosomal escape and mitochondria targeting - Qiuhao Ye; Jiao Wang; Ruotao Guo; Guizhi Chen; Yating Shen; Yijin Wu; Jingtang Wang; Zeyu Lin; Kun Wang; Jianling Chen; Yiru Peng (Journal of Photochemistry and Photobiology B: Biology, 2024)

Self-powered wearable human-computer interaction system based on kapok cellulose nanofibers - Yating Shi; Changmei Lin; Peiwei Deng; Leo N.Y. Cao; Weiguo Wang; Wanjing Li; Hezhi Lin; Yun Yang; Hao Wang; Meidan Ye; Zijie Xu; Shilin Cao; et al. (Chemical Engineering Journal, 2024)

Effects of exopolysaccharide by Pediococcus acidilactici S1 on the gelation properties and microstructure of porcine myofibrillar protein - Peiran Lu; Lin Mei; Xinran Wang; Yating Wu; Guoguo Jin; Man Zhang (Food Hydrocolloids, 2024)

Impact of ethanol extract of propolis on heat-induced egg white protein gels: Formation and properties - Man Zhang; Lin Mei; Yating Wu; Guoguo Jin; Di Bao (Food Hydrocolloids, 2024)

A versatile CuCo@PDA nanozyme-based aptamer-mediated lateral flow assay for highly sensitive, on-site and dual-readout detection of Aflatoxin B1 - Xu Zhu; Jing Tang; Xilian Ouyang; Yibo Liao; Haopeng Feng; Jiangfang Yu; Li Chen; Yating Lu; Yuyang Yi; Lin Tang (Journal of Hazardous Materials, 2024)

Identification a novel Ganoderma FIP gene from Ganoderma capense and its functional expression in Pichia pastoris - Jingwei Lin; Yating Liao; Sijia Yang; Taicheng Jin; Boning Yu; Kai Zhao; Yixiao Sai; Cheng Lin; Yanhua Song; Hui Ma; Zhanyong Wang (World Journal of Microbiology and Biotechnology, 2024)

Degradation of iopamidol in the permanganate/sulfite process: Evolution of iodine species and effect on the subsequent formation of disinfection by-products - Yimin Lin; Hongyu Dong; Yating Zhu; Gongming Zhou; Junlian Qiao; Xiaohong Guan (Journal of Environmental Sciences, 2024)

Chitosan composite films based on tea seed oil nano-microcapsules: Antibacterial, antioxidant and physicochemical properties - Qiuya Ji; Zhou Jin; Wanlu Ding; Yating Wu; Chunjie Liu; Kang Yu; Nannan Zhang; Guoguo Jin; Peiran Lu; Di Bao; Lin Mei (Food Packaging and Shelf Life, 2023)

Associations of 10 trace element levels in the whole blood with risk of three types of obesity in the elderly - Rui Zhan; Lin Liu; Maoyuan Yang; Yating Ren; Zhihao Ge; Jun Shi; Ke Zhou; Jiebao Zhang; Hongjuan Cao; Linsheng Yang; Kaiyong Liu; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

Fluorine grafted gel polymer electrolyte by in situ construction for high-voltage lithium metal batteries - Junqiao Huang; Zhichuan Shen; Stuart J. Robertson; Yuhan Lin; Junli Zhu; Kun Yang; Yating Wang; Minhua Shao; Zhicong Shi (Chemical Engineering Journal, 2023)

Study on the formation pathways of characteristic volatiles in preserved egg yolk caused by lipid species during pickling - Zhuosi Yu; Lin Ye; Yating He; Xinhong Lu; Le Chen; Shiqin Dong; Xiaole Xiang (Food Chemistry, 2023)

The underappreciated importance of solar radiation in constraining spring phenology of temperate ecosystems in the Northern and Eastern United States - Yating Gu; Yingyi Zhao; Zhengfei Guo; Lin Meng; Kun Zhang; Jing Wang; Calvin K.F. Lee; Jing Xie; Yantian Wang; Zhengbing Yan; He Zhang; Jin Wu (Remote Sensing of Environment, 2023)

A Novel Near-Infrared Ratiometric Fluorescence Probe for Hg2+ Based on Quinoline-Fused Rhodamine Dye - Weiping Lai; Yanfei Lin; Tianqing Ye; Yating Yu; Hongwei Zhou; Lei Li; Guoliang Mao; Jianbo Wang (Journal of Fluorescence, 2023)

To close or open the tank input water valve: Secondary water-supply systems with double tanks will induce a higher microbial risk - Dong Hu; Wenfang Lin; Jie Zeng; Heng Zhang; Yating Wei; Xin Yu (Science of The Total Environment, 2023)

Design and fabrication of anthocyanin functionalized layered clay/poly(vinyl alcohol) coatings on poly(lactic acid) film for active food packaging - Long Mao; Chengyu Wang; Jin Yao; Yating Lin; Xinxin Liao; Jing Lu (Food Packaging and Shelf Life, 2023)

“Dark under the lamp”: ecological equity of urban agglomeration from the perspective of natural capital in China - Hui Zhang; Yating Dai; Dao-lin Zhu (Environmental Science and Pollution Research, 2023)

Hippocampal Iron Accumulation Impairs Synapses and Memory via Suppressing Furin Expression and Downregulating BDNF Maturation - Yating Zhang; Xue Bai; Yi Zhang; Shanshan Yao; Yiduo Cui; Lin-Hao You; Peng Yu; Yan-Zhong Chang; Guofen Gao (Molecular Neurobiology, 2022)

Recognition of behavior state of Penaeus vannamei based on passive acoustic technology - Maochun Wei; Keyu Chen; Yating Lin; En Cheng (Frontiers in Marine Science, 2022)
Underwater signal processing based on passive acoustic technology has carried out a lot of research on the behavioral sound of underwater creatures and the protection of marine resources, which proves the feasibility of passive acoustic technology for long-term and non-destructive monitoring of underwater biological sound production. However, at present, most relevant research focuses on fish but little research on shrimp. At the same time, as the main economic breeding industry, Penaeus vannamei has a backward industrial structure, in which the level of intelligence needs to be improved. In this paper, the acoustic signals generated by different physiological behaviors of P. vannamei are collected based on passive acoustic technology. Their different behaviors are finally classified and identified through feature extraction and analysis. Meanwhile, the characteristic non-parametric ANOVA is carried out to explore the relationship between the acoustic signals and the behavior state of P. vannamei to achieve the purpose of real-time monitoring of the behavior state of P. vannamei . The experimental results show that linear prediction cepstrum coefficient (LPCC) and Mel-frequency cepstrum coefficient (MFCC) characteristic coefficients are effective in the classification and recognition of different behavioral acoustic signals with interspecific acoustic signals of P. vannamei . Meanwhile, the SVM classifier based on OvR classification strategy can model the acoustic signal characteristics of different underwater biological behaviors more efficiently and has classification accuracy as high as 93%.

Multifunctional Role of Silica in Pharmaceutical Formulations - Yating Gao; Yue Zhang; Yanlong Hong; Fei Wu; Lan Shen; Youjie Wang; Xiao Lin (AAPS PharmSciTech, 2022)

The contrasting effects of thermodynamic and dynamic processes on East Asian summer monsoon precipitation during the Last Glacial Maximum: a data-model comparison - Yong Sun; Haibin Wu; Masa Kageyama; Gilles Ramstein; Laurent Z. X. Li; Ning Tan; Yating Lin; Bo Liu; Weipeng Zheng; Wenchao Zhang; Liwei Zou; Tianjun Zhou (Climate Dynamics, 2021)
The Last Glacial Maximum (LGM; 21 ka BP) was the most recent glacial period when the global ice sheet volume was at a maximum. Therefore, the LGM can be used to investigate atmospheric dynamics under a climate that differed significantly from the present. This study quantitatively compares pollen records of boreal summer (June–July–August) precipitation with the PMIP3 LGM simulations. The data-model comparison shows an overall agreement on a drier than pre-industrial East Asian summer monsoon (EASM) climate. Nevertheless, 17 out of 55 records show a regional precipitation increase that is also simulated over the additional land mass area due to sea level drop. The thermodynamic and dynamic responses are analyzed to explain a drier LGM EASM as a combination of these two antagonistic mechanisms. Relatively low atmospheric moisture content was the main thermodynamic control on the lower LGM (relative to pre-industrial levels) EASM precipitation amounts in both the reconstructions and the models. In contrast, two dynamic processes in relation to stationary eddy activity act to increase EASM precipitation regionally in records and simulations, respectively. Precipitation increase in records is explained by dynamic enhancement of the horizontal moisture transport, while dynamic enhancement of the vertical moisture transport leads to simulated precipitation increase over the specific region where landmass was exposed during LGM along continental coastlines of China due to significant drop in sea level (relative to pre-industrial levels). Overall, the opposing effects of thermodynamic and dynamic processes on precipitation during the LGM provide a means to reconcile the spatial heterogeneity of recorded precipitation changes in sign, although data-model comparison suggests that the simulated dynamic wetting mechanism is too weak relative to the thermodynamic drying mechanism over data-model disagreement regions.

Quantitative climatic reconstruction of the Last Glacial Maximum in China - Haibin Wu; Qin Li; Yanyan Yu; Aizhi Sun; Yating Lin; Wenqi Jiang; Yunli Luo (Science China Earth Sciences, 2019)

Evolution of the relative abundance of C 4 plants on the Chinese Loess Plateau since the Last Glacial Maximum and its implications - Wenqi Jiang; Jianyu Wu; Haibin Wu; Qin Li; Yating Lin; Yanyan Yu (Journal of Quaternary Science, 2019)
Understanding the distribution of C 3 and C 4 plants and its forcing mechanisms since the Last Glacial Maximum (LGM) is important for anticipating their possible response to future climate change. The spatiotemporal pattern of C 4 plant abundance on the Chinese Loess Plateau (CLP) is complex and the dominant causal factors are contentious. Here, we use δ 13 C records of organic matter in paleosols from the CLP to reconstruct changes in the representation of C 4 plants since the LGM. The results indicate that the relative abundance of C 4 plants increased after the LGM, reaching a maximum during 10–6 ka bp, and then decreased. Spatially, the representation of C 4 plants was characterized by increasing values from north‐west to south‐east. In addition, the smallest spatial difference (∼10%) in the representation of C 4 plants between the north‐west and south‐east parts of the CLP was during the LGM, and the largest difference (∼30%) was during the early Holocene. We combined our findings with output from the BIOME4 model to study the sensitivity of C 4 plants to changes in climate and atmospheric CO 2 concentration. The results suggest that increasing temperature was the dominant factor driving C 4 plant expansion on the CLP since the LGM.

Isolation and Analysis of Salt Response of Lactobacillus plantarum FS5-5 from Dajiang - Xuefei Song; Qianqian Wang; Xin Xu; Jingwei Lin; Xiaorui Wang; Yating Xue; Rina Wu; Yingfeng An (Indian Journal of Microbiology, 2016)